# Solve the differential equation 2y"+20y'+51y=0, y(0)=2 y'(0)=0 Question
Differential equations Solve the differential equation $$2y"+20y'+51y=0, y(0)=2$$
$$y'(0)=0$$ 2021-02-09
Step 1
Let $$y=e^{mt}$$ be a trial solution. Then the auxiliary equation is given by $$2m^{2}+20m+51=0 as e^{mt}\neq0$$, for all t
Thus the solutions of auxiliary equations are
$$m= -5\pm i\sqrt{\frac{2}{2}}$$
Therefore the solution of the differential equation is given by
$$y= e^{-5}(c_{1}\cos(\frac{t}{\sqrt 2})+c_{2}\\sin(\frac{t}{\sqrt 2}))$$
Now apply initial condition
$$y(0)= e^{-5\times0}(c_{1}\cos(\frac{0}{\sqrt 2})+c_{2}\\sin(\frac{0}{\sqrt 2}))= 1\times(\cos(0)c_{1}+\\sin(0)c_{2})=c_{1}$$
Thus y(0)=2 gives us $$c_{1}=2$$
Step 2
Further by allpying the product rule of differention we get
$$y'(x)=(e^{-5t})(c_{1}\cos(\frac{t}{\sqrt 2})+c_{2}\\sin(\frac{t}{\sqrt 2}))+(c_{1}(\frac{t}{\sqrt 2})+c_{2}\sin(\frac{t}{\sqrt 2}))' e^{-5t}$$
$$=(-5e^{-5t})(c_{1}\cos(\frac{t}{\sqrt 2})+c_{2}\sin(\frac{t}{\sqrt 2}))+(-c_{1}\sin(\frac{t}{\sqrt 2})+c_{2}cos(\frac{t}{\sqrt 2}))\sqrt 2 e^{-5t}$$
$$= -5e^{-5t}(c_{1}\cos(\frac{t}{\sqrt 2})+c_{2}\sin(\frac{t}{\sqrt 2}))+(e^{-5t}(-c_{1}\sin(\frac{t}{\sqrt 2})+c_{2}\cos(\frac{t}{\sqrt 2}))\sqrt 2$$
Notice that
$$y'(0)= -5e^{-5*0}(c_{1}\cos(\frac{0}{\sqrt 2})+c_{2}\sin(\frac{0}{\sqrt 2}))+(e^{-5*0}(-c_{1}\sin(\frac{0}{\sqrt 2})+c_{2}\cos(\frac{0}{\sqrt 2}))\sqrt 2$$
$$= -5e^{5*0}(\cos(0)c_{1}+\sin(0)c_{2})+(e^{-5*0}(\cos(0)c_{2}-\sin(0)c_{1}))\sqrt 2= -5c_{1}+c_{2}\sqrt 2$$
Now y'(0)=0 gives us
$$-5c_{1}+c_{2}\sqrt 2=0 \implies -10+c_{2}\sqrt 2=0 \ [\because c_{1}=2]$$
$$\implies c_{2}=10\sqrt 2$$
Therefore the required solution is given by
$$y= e^{-5t}(2\cos(\frac{t}{\sqrt 2})+10\sqrt 2\sin(\frac{t}{\sqrt 2}))$$

### Relevant Questions Solve differential equation: $$\displaystyle{y}'+{y}^{{2}}{\sin{{x}}}={0}$$ Solve the differential equations
(1) $$\displaystyle{x}{y}'-{2}{y}={x}^{{3}}{e}^{{x}}$$
(2) $$\displaystyle{\left({2}{y}{\left.{d}{x}\right.}+{\left.{d}{y}\right.}\right)}{e}^{{2}}{x}={0}$$ Solve the Differential equations $$\displaystyle{\left({D}^{{3}}−{3}{D}+{2}\right)}{y}={0}$$ Solve the initial value problem.
$$\displaystyle{4}{x}^{{2}}{y}{''}+{17}{y}={0},{y}{\left({1}\right)}=-{1},{y}'{\left({1}\right)}=-\frac{{1}}{{2}}$$ Give the correct answer and solve the given equation:
$$\displaystyle{x}{y}{\left.{d}{x}\right.}-{\left({y}+{2}\right)}{\left.{d}{y}\right.}={0}$$ solve the Differential equations $$\displaystyle{y}{'''}+{10}{y}{''}+{25}{y}'={0}$$ Solve the given system of differential equations.
\[Dx+Dy+(D+1)z=0\)
Dx+y=e^{t}\)
Dx+y-2z=50\sin(2t)\) $$\displaystyle{\frac{{{\left({d}^{{{2}}}\right)}{y}}}{\rbrace}}{\left\lbrace{d}{\left({t}^{{{2}}}\right\rbrace}+{4}{\left({\frac{{{\left.{d}{y}\right.}}}{{{\left.{d}{t}\right.}}}}+{3}{y}={e}^{{-{t}}}\right.}\right.}$$ Solve the Differential equations $$y'' + 4y = 4 \tan^{2} x$$ The coefficient matrix for a system of linear differential equations of the form $$\displaystyle{y}^{{{1}}}={A}_{{{y}}}$$ has the given eigenvalues and eigenspace bases. Find the general solution for the system.
$$\displaystyle{\left[\lambda_{{{1}}}=-{1}\Rightarrow\le{f}{t}{\left\lbrace{b}{e}{g}\in{\left\lbrace{b}{m}{a}{t}{r}{i}{x}\right\rbrace}{1}{0}{3}{e}{n}{d}{\left\lbrace{b}{m}{a}{t}{r}{i}{x}\right\rbrace}{r}{i}{g}{h}{t}\right\rbrace},\lambda_{{{2}}}={3}{i}\Rightarrow\le{f}{t}{\left\lbrace{b}{e}{g}\in{\left\lbrace{b}{m}{a}{t}{r}{i}{x}\right\rbrace}{2}-{i}{1}+{i}{7}{i}{e}{n}{d}{\left\lbrace{b}{m}{a}{t}{r}{i}{x}\right\rbrace}{r}{i}{g}{h}{t}\right\rbrace},\lambda_{{3}}=-{3}{i}\Rightarrow\le{f}{t}{\left\lbrace{b}{e}{g}\in{\left\lbrace{b}{m}{a}{t}{r}{i}{x}\right\rbrace}{2}+{i}{1}-{i}-{7}{i}{e}{n}{d}{\left\lbrace{b}{m}{a}{t}{r}{i}{x}\right\rbrace}{r}{i}{g}{h}{t}\right\rbrace}\right]}$$